Analisis Kondisi Fisik dan Psikis Terhadap Kemampuan Smash Kedeng Sepak Takraw - Bemba, Tonia; Riswanto, Heri; Saman, Saman; Hidayat, Rachmat; Ainun, Nur; Muallin, Muallin (Universitas Hamzanwadi, 2025)
This study aims to examine the relationship between physical and psychological conditions on the ability to smash kedeng sepak takraw. This method uses descriptive quantitative. The population of this study was sepak takraw extracurricular students of SMAN 5 Palopo, a sample of 12 students. Research instruments and data collection techniques using leg muscle strength tests, leg explosive power tests, flexibility tests, motivation tests, self-confidence tests, kedeng smash accuracy tests. Data processing using SPSS. The results of the research F value of physical condition of smash kedeng 48.132, a significant value of 0.000 then H1 is accepted which shows X1 has a significant influence on Y, the R value of 0.910 indicates that the ability of the dependent variable is strong. The F value of psychic smash kedeng 25.424 and a significant value of 0.001 then H2 is accepted which shows X2 has a significant effect on Y, the R value of 0.847 indicates that the ability of the dependent variable is strong. While the F value of physical and psychological conditions for kedeng smash is 39.852 and a significant value of 0.000, H3 is accepted which shows X1-X2 have a significant effect on variable Y, the R value of 0.948 indicates that the ability of the dependent variable is strong. It is concluded that the regression test shows a positive relationship between physical and psychological conditions with the ability to smash kedeng.